2013
DOI: 10.1016/j.dza.2013.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Objectifying acupuncture effects by lung function and numeric rating scale in patients undergoing heart surgery

Abstract: Rationale. Poststernotomy pain and impaired breathing are common clinical problems in early postoperative care following heart surgery. Insufficiently treated pain increases the risk of pulmonary complications. High-dose opioids are used for pain management, but they may cause side effects such as respiratory depression. Study Design. We performed a prospective, randomized, controlled, observer-blinded, three-armed clinical trial with 100 patients. Group 1 ( = 33) and Group 2 ( = 34) received one 20 min sessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Similarly, pooled results from 24 trials showed that body APS significantly improved VAS scores in comparison with all control groups ( P < 0.00001), and subgroup analyses revealed similar improvement compared with standard treatment ( P < 0.00001) and sham/placebo control ( P < 0.0001; Table 5 ). The evidence for body points APS reducing postoperative pain intensity in surgery patients was determined to be of Level I quality based on six overall high quality RCTs [ 14 , 23 , 47 , 49 , 52 , 58 ]. A meta-analysis of pooled results and subgroup analyses of body EA, as well as invasive and noninvasive forms of this treatment, yielded similar results ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, pooled results from 24 trials showed that body APS significantly improved VAS scores in comparison with all control groups ( P < 0.00001), and subgroup analyses revealed similar improvement compared with standard treatment ( P < 0.00001) and sham/placebo control ( P < 0.0001; Table 5 ). The evidence for body points APS reducing postoperative pain intensity in surgery patients was determined to be of Level I quality based on six overall high quality RCTs [ 14 , 23 , 47 , 49 , 52 , 58 ]. A meta-analysis of pooled results and subgroup analyses of body EA, as well as invasive and noninvasive forms of this treatment, yielded similar results ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%